2016
DOI: 10.7860/jcdr/2016/15404.7097
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Vitamin D Deficiency and Severity of Chronic Obstructive Pulmonary Disease-A Case Control Study

Abstract: COPD was associated with an increased risk of vitamin D deficiency, and there was a significant association between vitamin D levels and Combined COPD stage severity. Also, a higher pack year and a low BMI are associated with lower levels of vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Results of this study were not consistent with the study of Sanket et al, [12] that COPD was associated with the risk increase of vitamin D deficiency, and there was a significant association between level vitamin D and severity of COPD. Zhu et al, (2015) [33] investigated the association between host serum 25-hydroxyvitamin D (25(OH)D) and the susceptibility and severity of COPD and found that low serum levels of 25(OH)D were not associated with COPD susceptibility, but the high deficiency rate of 25(OH)D was associated with COPD severity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results of this study were not consistent with the study of Sanket et al, [12] that COPD was associated with the risk increase of vitamin D deficiency, and there was a significant association between level vitamin D and severity of COPD. Zhu et al, (2015) [33] investigated the association between host serum 25-hydroxyvitamin D (25(OH)D) and the susceptibility and severity of COPD and found that low serum levels of 25(OH)D were not associated with COPD susceptibility, but the high deficiency rate of 25(OH)D was associated with COPD severity.…”
Section: Discussioncontrasting
confidence: 99%
“…Of 50 study subjects, the majority of them were male accounted for 47 patients (94%) and 3 females (6%), and the majority of the study subjects are in the category of age older than 60 years old. Results of this study are consistent with those of the case-control study conducted by Sanket et al, for 81 COPD patients that consisted of 75 males (92.5%) [12]. The higher prevalence rate of COPD for the male group is associated with a higher prevalence rate of smokers for males compared to females [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, vitamin D deficiency has been shown in several pathology related to higher incidence of stroke. Shah Sanket et al reported that Vitamin D deficiency was observed in significant number of patients with Chronic obstructive pulmonary disease (COPD) and in more than half of the study subjects, there is an increasing frequency across combined COPD class of cardiovascular and cerebrovascular disease [154]. Moreover, stroke patients with enough vitamin D had more favorable outcomes, including improved muscle strength and bone density.…”
Section: Vitamin D Deficiency and Ischemic Strokementioning
confidence: 99%
“…[36] In another study from Ethiopia, it was found that vitamin-D deficiency was significantly associated overweight and obese school children. [37]…”
Section: Discussionmentioning
confidence: 99%